La distribution on the crater surface of W‐1%La2O3 produced by a single laser pulse. (3rd June 2020) - Kaciulis, Saulius; Mezzi, Alessio; Montanari, Roberto; Richetta, Maria; Pakhomova, Ekaterina; Varone, Alessandra
Abstract : The W‐1%La2 O3 alloy has been irradiated by a single laser pulse (λ = 1064 nm) to simulate transient thermal loads of high energy occurring in a tokamak under operative conditions. A zone with a diameter of ~2 mm, namely, much larger than the focal spot, results to be affected by the pulse, and a crater of about 300 μm is observed in its center. La2 O3 particles are not present inside the crater. The change of surface morphology is accompanied by elemental redistribution. Multipoint XPS analysis evidenced that the concentration of La is very low in the crater and increases moving toward the border of the affected zone while that of W shows an opposite trend. The composition changes involve only the outmost 5 nm of the sample: through depth profiling, no differences of chemical composition were detected deeper in the alloy between the center and external border of the affected area.